Unusual substitutional properties of Cu in bulk polycrystalline samples of La₀.₇Ca₀.₃Mn₁₋xCuxO₃₋δ - Tovstolytkin, A.I.; Pogorilyi, A.N.; Belous, O.Z.; Yanchevski, A.G. (Физика низких температур, 2001)
The transport and magnetoresistive properties of bulk polycrystalline samples of the La₀.₇Ca₀.₃Mn₁₋xCuxO₃₋δ (x ≤

0.15) system are studied in the temperature range 77 K-300 K. All the samples investigated exhibit the giant magnetoresistance effect

associated with the transition from the ferromagnetic metallic to the paramagnetic insulating state. As a function of copper concentration,

the temperature of the resistivity peak, Tp, first decreases from 193 K (x=0) to 108 K (x=0.10) and then gradually grows, reaching 120 K at

x=0.15. Significant temperature broadening of the resistive transition as well as anomalous behavior of the peak value of the resistivity

are observed near x=0.10. The unusual properties of the La0.7Ca0.3Mn1-xCuxO3-d system are well explained in terms of a mixed valence of the

Cu ions.
The transport and magnetoresistive properties of bulk polycrystalline samples of the La₀.₇Ca₀.₃Mn₁₋xCuxO₃₋δ (x=0.15) system are

studied in the temperature range 77 K–300 K. All the samples investigated exhibit the giant magnetoresistance effect associated with the

transition from the ferromagnetic metallic to the paramagnetic insulating state. As a function of copper concentration, the temperature Tp

of the resistivity peak first decreases from 193 K (x=0) to 108 K (x=0.10) and then gradually grows, reaching 120 K at x=0.15. Significant

temperature broadening of the resistive transition as well as anomalous behavior of the peak value of the resistivity are observed near

x=0.10. The unusual properties of the La₀.₇Ca₀.₃Mn₁₋xCuxO₃₋δ system are well explained in terms of a mixed valence of the Cu ions.